Effects of organic and inorganic fertilizers on the growth and yield of rodent tuber (Typhonium flagelliforme) - Mat Napi, Mohamad Faiz (2015)
Typhonium flagelliforme, known also as Rodent Tuber (English) or Keladi Tikus (Malay), is an important herbal plant used by local communities as an alternative therapy in Malaysia and Indonesia to treat various types of cancer. Rodent tuber is a medicinal herb which belongs to the Araceae family with a maximum height of 25 to 30 cm. Recently, the planting of rodent tuber in Kelantan, especially in Kok Lanas, Kota Bharu faces a problem of low yield. The size of tuber becomes increasingly small and the flowering is late. A short-term field experiment was conducted on rodent tuber to assess the effects of inorganic fertilizer, organic fertilizer and integrated use of both fertilizers on plant growth and yields. Four treatments were used: cow manure + compost (T1), NPK Green + compost (T2), chemical fertilizer (NKP Green) (T3) and Compost (T4). The results showed that there were significant differences in growth and yield of Typhonium flagelliforme between the treatments (P<0.05). It was found that the application of organic fertilizers increased the yield and growth of the rodent tuber plant more than inorganic fertilizer. Compost application was the best management system for increasing rodent tuber yield both the tuber and leave parts.